Metabolic responses to sulfur dioxide in grapevine (Vitis vinifera L.): photosynthetic tissues and berries - Considine, Michael J.; Foyer, Christine H. (Frontiers in Plant Science, 2015)
Research on sulfur metabolism in plants has historically been undertaken within the context of industrial pollution. Resolution of the problem of sulfur pollution has led to sulfur deficiency in many soils. Key questions remain concerning how different plant organs deal with reactive and potentially toxic sulfur metabolites. In this review, we discuss sulfur dioxide/sulfite assimilation in grape berries in relation to gene expression and quality traits, features that remain significant to the food industry. We consider the intrinsic metabolism of sulfite and its consequences for fruit biology and postharvest physiology, comparing the different responses in fruit and leaves. We also highlight inconsistencies in what is considered the “ambient” environmental or industrial exposures to SO2. We discuss these findings in relation to the persistent threat to the table grape industry that intergovernmental agencies will revoke the industry’s exemption to the worldwide ban on the use of SO2 for preservation of fresh foods. Transcriptome profiling studies on fruit suggest that added value may accrue from effects of SO2 fumigation on the expression of genes encoding components involved in processes that underpin traits related to customer satisfaction, particularly in table grapes, where SO2 fumigation may extend for several months.